The Leveling of Environmental Polarization as a Part of Strategy of Perspective Innovation Policy of Economic Systems - Novikov, Aleksandr A.; Novikova, Elena V.; Moiseyeva, Elena V.; Fatikhova, Larisa E.; Ruzakova, Olga V.; Khairullin, Lenar R. (International Review of Management and Marketing, 2016)
The relevance of the article is reasoned by the strategies’ definition for perspective innovation policy of economic systems. In conditions of the Federal state entities’ autonomy strengthening one of the strategies for perspective innovative policy of economic systems is aimed at leveling of the environmental polarization as the basis for transition to innovative socially oriented type of economic development, reducing interregional differentiation in the level and quality of the population’s life, creation of equal opportunities for citizens and contributing to human development. The article is aimed at finding out of the specifics for spatial polarization’s leveling as a strategic component of perspective innovative policy of economic systems. A leading approach is the institutional approach that considers the environmental polarization as a socio-economic differentiation of regions on creation of worthy living conditions for citizens, complex development and competitiveness of the regional economy. The article clarifies the essence of selective support as a tool for leveling of the environmental polarization; presents the world experience of regions’ selective support in order to eliminate environmental socio-economic disparities; reveals the types of selective support (polarized, leveling incentive, leveling deterrent) and gives a comparative analysis of their aims, objects, tools. The paper submissions will be useful for specialists of Federal and regional authorities, local governments, line ministries, scientists who are interested in issues of regional economy and innovation policy of economic systems. Keywords: Environmental Polarization, Innovation Policy, Economic Systems, Interregional Differentiation. JEL Classifications: C15, F15, O31.